Cross-cultural validation of the Italian version of the Cumulated Ambulation Score. Issue 2 (June 2016) - Grana, Elisa; Verzellotti, Simone; Grassi, Federico A.; Ferriero, Giorgio; Kristensen, Morten T.; Cisari, Carlo; Invernizzi, Marco
Abstract : Hip fractures are common in elderly patients, and walking impairment is a frequent complication. The Cumulated Ambulation Score (CAS) is a validated functional scale used to monitor easily three basic mobility activities in patients with hip fracture. The aim of this study was to translate, cross-cultural adapt, and validate the CAS in the Italian language (CAS-I). The translation was carried out according to recommended guidelines. The final version of the CAS-I was administered to 80 geriatric patients with hip fracture admitted to a Traumatology Unit, and allowed full weight-bearing after treatment with hemiarthroplasty. Two raters evaluated each patient 2 days after surgery and then after 3 months. Statistical methods included Cronbach's α coefficient for the scale's internal consistency; the total agreement; and the κ coefficient for the inter-rater reliability. The concurrent validity of the scale was determined by comparing the total CAS-I (0–6 points) with the Index of Independence in Activities of Daily Living score (0–4 points). Internal consistency and inter-rater reliability of the CAS, evaluated with Cronbach's α and κ, respectively, were above 0.84 and 0.94. The SE of measurement for the total CAS-I (0–6 points) 2 days and 3 months after surgery were 0.03 and 0.13 points, respectively. The CAS-I showed a significant correlation with the first four items of the Activities of Daily Living score scale ( r ≥0.85, P <0.001). This study confirms the validity of the CAS-I for patients with a hemiarthroplasty after hip fracture and provides additional evidence of the psychometric properties of the scale. We suggest that the official CAS-I version be used in other settings to evaluate the basic mobility in patients with hip fracture.